2014
DOI: 10.1155/2014/465760
|View full text |Cite
|
Sign up to set email alerts
|

Differential Activation Patterns of fMRI in Sleep‐Deprived Brain: Restoring Effects of Acupuncture

Abstract: Previous studies suggested a remediation role of acupuncture in insomnia, and acupuncture also has been used in insomnia empirically and clinically. In this study, we employed fMRI to test the role of acupuncture in sleep deprivation (SD). Sixteen healthy volunteers (8 males) were recruited and scheduled for three fMRI scanning procedures, one following the individual's normal sleep and received acupuncture SP6 (NOR group) and the other two after 24 h of total SD with acupuncture on SP6 (SD group) or sham (Sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 36 publications
1
23
0
Order By: Relevance
“…A summary of clinic insomnia research confirmed the clinical effects of acupuncture for insomnia [8]. The present experiment demonstrated that acupuncture was activated specific cortex regions and showed significant difference with sham acupuncture group in SD patients [9]. Previous research suggested that according to the polysomnogram recorded, acupuncture was effectively enhanced the quality of sleep [10].…”
Section: Introductionsupporting
confidence: 72%
“…A summary of clinic insomnia research confirmed the clinical effects of acupuncture for insomnia [8]. The present experiment demonstrated that acupuncture was activated specific cortex regions and showed significant difference with sham acupuncture group in SD patients [9]. Previous research suggested that according to the polysomnogram recorded, acupuncture was effectively enhanced the quality of sleep [10].…”
Section: Introductionsupporting
confidence: 72%
“…This group, in addition to providing equal nutrition and blood supply to various parts of the body cells, transfer proper energy to different parts of the body cells through the regulation of the body's energy in energy channels and chakras. In this regard, it strengthens individuals' central and peripheral nervous system, power, and physical strength [18][19][20][21][22].…”
Section: Resultsmentioning
confidence: 99%
“…Animal research has indicated that electroacupuncture at GV26 improves neurological function in rats following cerebral ischemia/reperfusion injury, and may be associated with down-regulation of BKCa channel protein and mRNA expression [34]. fMRI studies revealed that acupuncture at SP6 could induce changes in neural activity in the sensorimotor cortical network of a sleep-deprived brain [35]. Auricular acupuncture (AA)…”
Section: Discussionmentioning
confidence: 99%